2021
DOI: 10.2147/jpr.s313513
|View full text |Cite
|
Sign up to set email alerts
|

Pain Medicine Fellowship Program Websites in the United States of America – A Nonparametric Statistic Analysis of 14 Different Criteria

Abstract: Methods: We obtained a list of accredited 104 Pain Medicine Fellowship Program websites from the Accreditation Council for Graduate Medical Education and the Electronic Residency Application Service. Individual Pain Medicine Fellowship Program websites were then evaluated on 14 different criteria. We grouped fellowship programs based on census region and Electronic Residency Application Service participation status, and analyzed the differences using nonparametric statistics. Results: A total of 104 accredited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
2
Order By: Relevance
“…Our finding that there were no significant differences in website comprehensiveness among the four regions was consistent with many other studies on neurology fellowship websites. 13 , 15 , 22 , 23 Although our study showed that ERAS-participation status influenced website comprehensiveness, a study on pain medicine fellowship websites did not find this result significant. 22 We predict that programs that do not participate in ERAS may not rely on websites to provide information to applicants, as they may prefer different methods of communication.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Our finding that there were no significant differences in website comprehensiveness among the four regions was consistent with many other studies on neurology fellowship websites. 13 , 15 , 22 , 23 Although our study showed that ERAS-participation status influenced website comprehensiveness, a study on pain medicine fellowship websites did not find this result significant. 22 We predict that programs that do not participate in ERAS may not rely on websites to provide information to applicants, as they may prefer different methods of communication.…”
Section: Discussioncontrasting
confidence: 73%
“… 13 , 15 , 22 , 23 Although our study showed that ERAS-participation status influenced website comprehensiveness, a study on pain medicine fellowship websites did not find this result significant. 22 We predict that programs that do not participate in ERAS may not rely on websites to provide information to applicants, as they may prefer different methods of communication. Future studies can examine the usage and effectiveness of other virtual platforms such as social media by non-ERAS-participating programs and ERAS-participating programs.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…For each recruitment and education variable assessed, outcomes were recorded as the presence or absence of the variable being assessed (►Table 1). [2][3][4][5][6] Web Site Recruitment and Education…”
Section: Web Site Analysismentioning
confidence: 99%
“…Although previous analyses have been conducted regarding fellowship Web site quality for other medical specialties, including orthopaedic surgery, 3 vascular surgery, 4 interventional radiology, 5 pain medicine, 6 and functional neurosur-gery, 2 no prior study has evaluated the quality, accessibility, or availability of online information for skull base fellowship programs. Therefore, the objective of this study is to evaluate all currently accessible information pertaining to existing skull base fellowship information repositories (-NASBS/AANS/ARS/ANS) and to evaluate the extent of information available on program-specific Web sites.…”
Section: Introductionmentioning
confidence: 99%